2022
DOI: 10.4103/ua.ua_1_21
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study on the predictability of Triple-D score versus Quadruple-D score in the success rate of extracorporeal shock wave lithotripsy of renal stones 1–2 cm in diameter

Abstract: Introduction: The aim of the study is to evaluate the clinical efficacy of Triple-D scoring system versus Quadruple-D scoring system for assessing stone-free rate (SFR) in individuals with renal stones measuring 1–2 cm in diameter after extracorporeal shock wave lithotripsy (ESWL). Materials and Methods: The study was conducted on 120 patients who presented to a tertiary care center in eastern India. Systemic random sampling technique was applied with a sampling interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…They found a parallel increase in SFR with an increase in the total score value, proving the validity of this model as an independent predictor. [5] Although we did not implement this model because of the retrospective pattern of the data, which was not available for certain items, our results showed significant differences in SFR relative to the stone size, largest diameter, and HU. Many other studies have reported similar outcomes for these factors for predicting SFR after SWL.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…They found a parallel increase in SFR with an increase in the total score value, proving the validity of this model as an independent predictor. [5] Although we did not implement this model because of the retrospective pattern of the data, which was not available for certain items, our results showed significant differences in SFR relative to the stone size, largest diameter, and HU. Many other studies have reported similar outcomes for these factors for predicting SFR after SWL.…”
Section: Discussionmentioning
confidence: 95%
“…[1] Skin-to-stone distance with stone density and dimension or volume is the components of a predictive model for the response to SWL, known as the Triple-D score. [2,5] Sengupta et al [5] evaluated the applicability of the Triple-D score in predicting SFR after a single-session SWL for stones measuring 10 to 20 mm. They found a parallel increase in SFR with an increase in the total score value, proving the validity of this model as an independent predictor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations